The Effect of Different Glycerol Concentrations to Milk Extender on Sperm Quality of Sheat-Fish (Ompok rhadinurus Ng, 2003) During Short Storage - Rizky Royhan Sitompul; Hamdan Alawi; Nuraini Nuraini (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2019)
ABSTRACTThe study was conducted on March in the Laboratory of Fish Hatchery and Breeding at the Faculty of Fisheries and Marine Sciences and Photomicrograph Laboratoryat The Faculty of Mathematics and Natural Sciences, University of Riau. The aim of this study was to evaluate the effect of different glycerol concentrations to milk extender on sperm motility, viability, fertility and hatching rate of sheat-fish (Ompok rhadinurus Ng, 2003) during short storage. This experiment useda Factorial Complete Random Match (CRD) one factor with 5 treatments and 3 replications, namely: P0 : 0% Glycerol in 100% milk extender, P1 : 1% Glycerol in 99% milk extender, P2: 2% Glycerol in 98% milk extender, P3 : 3% Glycerol in 97% milk extender and P4 : 4% Glycerol in 96% milk extender. Semen of this experiment was found from 35 males of sheat-fish and stored in the refginerator with 4 oC of temperature. The result showed that different glycerol concentrations to milk extender significantly affected to sperm quality of self-fish (Ompok rhadinurus Ng, 2003) during 96 hours storage (P<0.05). The result showed that P4 (4% Glycerol on 96% Milk Extender) was the best treatment with 76 hours of optimal storage time, it caused by sperm motility that was still good (3) with 47,8% viability. The fertility in 12 hours of storage was 87% with 89,6% hatching rate. But in 96 hours of storage fertility decreased until 45,3% with 53,3% hatching rate. Keyword :Ompok rhadinurus Ng, 2003, Glycerol, Milk Extender, Sperm Quality